The unicity of best approximation in a space of compact operators - Kowynia, Joanna (Mathematica Scandinavica, 2011)
Chebyshev subspaces of $\mathcal{K}(c_0,c_0)$ are studied. A $k$-dimensional non-interpolating Chebyshev subspace is constructed. The unicity of best approximation in non-Chebyshev subspaces is considered.